Correlation between Completeness of Basic Immunization and Other Factors with the Incidence of Acute Respiratory Infection in Toddlers - Aris Susanto; Irwandy Tirtawidjaja; Ivan Riyanto Widjaya; Meyselina Iwan (Jurnal MedScientiae, 2023)
Acute Respiratory Infection (ARI) is a common disease that occurs in children under five. In developingcountries, the probability of the disease within an age group of toddlers estimated 29% cases perchild/year and in developed countries 5% cases per child / year. It shows that there are 156 millionnew cases per year in the world in which 151 million cases (96.7%) occur in developing countries.Episode cold on Toddlers in Indonesia estimated 2-3 times per year (Rudan et al Bulletin WHO 2008).This study aims to determine the correlation between the comprehensiveness of basic immunization andother factors in terms of ARI on toddler in Cipejeuh Wetan – Cirebon within January to October 2016.The factors that are examined include comprehensiveness of basic immunization, exclusivebreastfeeding, nutrition, smoking behavior in the home. The design study is cross-sectional. Samplingtechnique is cluster random sampling with the primary data source in 62 children under five yearsusing questionnaire. The analysis is Chi-square. The statistical test showed a significant correlationbetween ARI against nutrition (p=0.015), smoking behavior in the home (p=0.009).